TEKNIK PRODUKSI MASSAL IKAN RAINBOW SHINER Notropis chrosomus: UPAYA KOMERSIALISASI HASIL USAHA BUDIDAYA DI INDONESIA - Iskandar, Andri; Amelia Purnama, Rahma; Eny Indriastuti, Cecilia; Dermawan, Budi; Iqbal Kurniawinata, Mohamad (Jurnal Perikanan Pantura (JPP), 2026)
The rainbow shiner (Notropis chrosomus) is a promising alternative aquaculture commodity in Indonesia due to its high market demand and economic value. However, technical information on its hatchery breeding remains limited. This study aimed to describe hatchery-based culture techniques for rainbow shiner using a descriptive approach. The research was conducted at Tetra Aquaria, Sukabumi, West Java, by collecting both primary and secondary data, including fecundity, fertilization rate (FR), hatching rate (HR), and survival rate (SR). Results showed that natural spawning with a male-to-female ratio of 1:1 produced an FR of 82.3% and an HR of 84.9%. Larvae reared in open concrete tanks achieved an SR of 88.5%, while juveniles maintained in aquaria reached an SR of 94.1%. Velvet disease was effectively treated using immersion in a solution of blue copper and salt. This study demonstrates that hatchery-based culture of rainbow shiner can produce high-quality juveniles and holds strong potential as a sustainable aquaculture species to meet market demand without relying on wild capture.